Analisis Dampak Disiplin Kerja Terhadap Motivasi Pegawai (Study Kasus Di Bpsdm Provinsi Jambi) - Suwarto Suwarto (Ekonomis: Journal of Economics and Business, 2020)
The purpose of this study is to find out: (1) an overview of work discipline, and employee motivation at the Jambi Province Human Resources Development Agency. (2) To determine the effect of work discipline on employee motivation at the Jambi Province Human Resources Development Agency. This research is descriptive and verification. The population in this study are employees of the Jambi Province Human Resources Development Agency. The research sampling technique used Stratified Sampling technique. The total sample in this study was 50 respondents. Data were analyzed using 2 (two) ways, namely using descriptive analysis using a Likert scale. Descriptive research results indicate, the average level of respondents' answers to the variable work discipline (X) of 3,188. The average level of respondents' answers to the motivation variable (Y) was 3.113.